2020
DOI: 10.1007/s00127-020-01840-w
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of prevalence and risk factor profiles of prolonged grief disorder among French and Togolese bereaved adults

Abstract: Background With the introduction of the prolonged grief disorder (PGD) in the ICD-11 and most likely in the future DSM-5-TR, there is clinical need to examine cultural variations in grief phenomenon. We tested whether grief symptoms differ cross-culturally by examining the prevalence rates and predictors of PGD among French and Togolese bereaved individuals. Methods The sample comprised 235 widowed persons (73 French and 162 Togolese participants). They all completed the Prolonged Grief Scale-11 items. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Further, what seems perhaps little surprising was the high prevalence of both symptomatic classes (44.7% for the predominantly PGD class and 34.7% for the combined PGD and Depression class) when compared to previous LCA research. Also, the prevalence of the predominantly PGD class was two time higher than that reported in Togolese widowed persons (Kokou-Kpolou et al, 2020b). With respect to our sample characteristics, the relatively short bereavement-period set as a criterion for participation (i.e., a maximum of 5 year post-loss) may explain the elevated prevalence rates of the predominantly PGD class.…”
Section: Discussionmentioning
confidence: 47%
“…Further, what seems perhaps little surprising was the high prevalence of both symptomatic classes (44.7% for the predominantly PGD class and 34.7% for the combined PGD and Depression class) when compared to previous LCA research. Also, the prevalence of the predominantly PGD class was two time higher than that reported in Togolese widowed persons (Kokou-Kpolou et al, 2020b). With respect to our sample characteristics, the relatively short bereavement-period set as a criterion for participation (i.e., a maximum of 5 year post-loss) may explain the elevated prevalence rates of the predominantly PGD class.…”
Section: Discussionmentioning
confidence: 47%
“…As with this study participant, Daggett (2002) found that the support that spousally bereaved men received was generally short-lived. Implications of the current study finding are especially concerning, considering Kokou-Kpolou et al ' s (2020) finding that bereaved male Togolese participants were at a higher risk of experiencing prolonged grief disorder, compared to spousally bereaved women. However, the current study participant's receipt of emotional support from his daughter only might have coincided with the fact that she was the only one residing with the participant at the time, thereby automatically assuming the dual role of providing structural and emotional support.…”
Section: Social Support Received During Bereavementmentioning
confidence: 84%
“…Therefore, bereaved persons engage in adaptive grieving by oscillating between confronting and avoiding the loss through either focusing on the loss or "get[ting] on with other things" (Stroebe et al, 2005, p. 52) at different points of the grieving period. The role of distraction as a coping mechanism by bereaved spouses within the dual-process model has been acknowledged by Kokou-Kpolou et al (2020) in a study on a Togolese and French sample. Along with the current participants' reports, these observations illustrate the importance of the support or distraction from the loss that bereaved spouses can access outside the home, which they are systematically barred from seeking out during the traditional mourning period in the study context.…”
Section: Withdrawal Of Support Social Isolation and Stigmatization During Bereavementmentioning
confidence: 99%
“…The deaths framed as statistic also leaves the bereaved individuals feeling that the pain of their loss in undervalued. In addition, not only can grief be overlooked by society but patients and their families can also experience social stigma regarding COVID-19 losses (17).…”
Section: Disenfranchisement Imposed Externallymentioning
confidence: 99%